Toward a Greener Future: Investigating the Environmental Quality of Non-Green Trading in OECD Countries - van Ledden, Anke; Can, Muhlis; Brusselaers, Jan (Ekonomikalia Journal of Economics, 2024)
International trade is recognized as a key contributor to environmental degradation. However, researchers and policymakers do not distinguish between the trade of green and non-green products. The Non-Green Trade Openness Index was developed to examine the effect of non-green products on environmental quality. This study examines the effect of trading non-green products on environmental quality for 37 member countries of the Organization for Economic Co-operation and Development (OECD) from 2003 to 2016 in the context of the Environmental Kuznets Curve (EKC) framework. The results of the long-run estimation techniques employed (FMOLS, DOLS, Fixed and Random effects) confirm the EKC hypothesis and show a negative relationship between the Non-Green Trade Openness Index and greenhouse gas emissions, which serves as a proxy for environmental quality. This implies that when there is more non-green trade in OECD member countries, greenhouse gas emissions within these countries decrease. Dividing green and non-green products is important, empowering practitioners and policymakers to make informed choices and define a strategy for a sustainable future. Additionally, policy recommendations are provided to support policymakers in their efforts to combat climate change.